A Case Series of Etizolam in Opioid-Related Deaths. Issue 7 (24th February 2021) - Gevorkyan, Jirair; Kinyua, Juliet; Pearring, Sue; Rodda, Luke N
Abstract: Etizolam is a novel psychoactive substance and novel benzodiazepine of the thienotriazolodiazepine class, which has recently seen an increasing trend in use worldwide. We report a case series of 10 decedents with etizolam and opioids in their systems. Death investigation, expanded toxicology and medical investigation information were included for contextualization of etizolam in death. Etizolam was detected and confirmed within peripheral and cardiac blood, urine, vitreous humor and, in one case, gastric fluid, by liquid chromatography–tandem mass spectrometry and liquid chromatography–quadrupole time of flight mass spectrometry methodologies. Death investigation indicated nonmedical use of most drugs. Medical investigation commonly noted pulmonary edema, cardiomegaly and cerebral swelling. The majority of the decedents appeared to be unaware of the presence of etizolam and succumbed to the mixed drug toxicity of their routine depressant and narcotic analgesic drug of abuse in combination with etizolam. Etizolam use continues to be observed and poses as a potentially lethal contribution to multiple drug toxicity, especially in the age of the opioid crisis. Assessment of analytes like etizolam requires up-to-date methodologies and vigilance in testing to better characterize the toxicology and interpret the contribution to death.